CELL TYPE-SPECIFIC SYNAPTIC ENCODING OF ETHANOL EXPOSURE IN THE NUCLEUS ACCUMBENS SHELL - Jeanes, Zachary M. (2014)
Synaptic alterations in the nucleus accumbens (NAc) are crucial for the aberrant reward-associated learning that forms the foundation of drug dependence. Altered glutamatergic synaptic plasticity, in particular, is thought to be a vital component of the neurobiological underpinnings of addictive behavior. The development of bacterial artificial chromosome-eGFP (enhanced green fluorescent protein) transgenic mice that express eGFP driven by endogenous D1 dopamine receptor (D1R) promoters has now allowed investigation of the cell type-specific synaptic modifications in the NAc in response to drugs of abuse. In this study, we used whole-cell ex vivo slice electrophysiology in Drd1-eGFP mice to investigate cell type-specific alterations in NAc synaptic plasticity following ethanol exposure. Electrophysiological recordings were made from eGFP-expressing medium spiny neurons (D1+ MSNs) and non-eGFP expressing (putative D2 receptor-expressing) (D1− MSNs) from the shell subregion of the NAc. We observed low frequency-induced long-term depression (1Hz-LTD) of α-amino-3-hydroxy-5-methyl-isoxazole-4-propionic acid (AMPA)-mediated excitatory postsynaptic currents (EPSCs) solely in D1+ MSNs. However, 24 hours following 4 consecutive days of in vivo chronic intermittent ethanol (CIE) vapor exposure, 1Hz-LTD was conversely observed only in D1− MSNs, and now absent in D1+ MSNs. Complete recovery of the baseline plasticity phenotype in both cell types required a full 2 weeks of withdrawal from CIE vapor exposure. Thus, we observed a cell type-specificity of synaptic plasticity in the NAc shell, as well as, a gradual recovery of the pre-ethanol exposure plasticity state following extended withdrawal. These changes highlight the adaptability of NAc shell MSNs to the effects of ethanol exposure and may represent critical neuroadaptations underlying the development of ethanol dependence.